Utilizing personal values to explain people’s attitudes towards legal norms - Bilsky, Wolfgang (European journal of criminology, 2022)
The aim of this study is to clarify whether personal values explain delinquents? and non-delinquents? general attitudes towards legal norms. We expect that 10 basic personal values form a circular scale common to all individuals, both delinquents and non-delinquents, that people?s ratings of the importance of these 10 values predict their norm acceptance in a sinusoidal way, with higher predictability for delinquents, and that the correlations of personal values with norm acceptance are highest for those delinquents with a broad spectrum of offences. Finally, we expect that gender does not have an impact on these profiles, whereas controlling for age does. Our analyses are based on four studies on community crime prevention. The results are in line with the above expectations.